Diagnostic criteria for atopic dermatitis in adult Thai population - Rungsima Wanitphakdeedecha (2018)
Context: Atopic dermatitis is a common disease that is diagnosed by use of Hanifin, Lobitz and Rajka′s criteria based on patient history and clinical features. However these criteria are not suitable for population-based studies. Aims: The purpose of this study is to develop a minimum list of diagnostic criteria for atopic dermatitis that is sensitive, specific, reproducible, noninvasive, applicable to adult Thai population and easy to perform in population-based studies. Settings and Design: This study was conducted at Department of Dermatology, Faculty of Medicine Siriraj Hospital Mahidol University, Bangkok, Thailand. Materials and Methods: The new cases of typical mild to moderate atopic dermatitis and exactly age-matched and sex-matched controls presenting with an inflammatory skin disease other than atopic dermatitis were selected from Department of Dermatology, Faculty of Medicine Siriraj Hospital. Each subject was examined with reference to 31 clinically diagnostic features of atopic dermatitis proposed by Hanifin and Rajka. One hundred and forty patients (70 cases and 70 controls) were studied. Statistical Analysis Used: Sensitivity and specificity of each criterion was calculated using the dermatologist's diagnosis as the standard. Regression techniques were then used to derive a minimum set of diagnostic criteria. Results: Using multiple logistic regression techniques, a minimum set of diagnostic criteria for atopic dermatitis was derived: visible flexural dermatitis, history of flexural dermatitis, duration of rash >6 months and visible dry skin. Conclusions: A minimum list of diagnostic criteria for atopic dermatitis was derived that should be of use in Thai population-based studies.